2009
DOI: 10.1002/syn.20713
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine withdrawal produces a decrease in extracellular levels of dopamine in the nucleus accumbens that is lower in adolescent versus adult male rats

Abstract: The behavioral effects of nicotine withdrawal are lower in adolescent versus adult rats. However, the neurochemical mechanisms that mediate these developmental differences are unknown. Previous studies have shown that extracellular levels of dopamine in the nucleus accumbens (NAcc) are reduced in adult rats experiencing withdrawal. This study compared dopamine levels in the NAcc of male adolescent and adult rats experiencing nicotine withdrawal. Animals were prepared with subcutaneous pumps that delivered an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 49 publications
8
62
0
Order By: Relevance
“…Previous studies have shown that tonic DA activity is decreased in nicotine-dependent animals (18) and that precipitated withdrawal from chronic nicotine leads to decreased DA levels (38). Using defined electrophysiological methods to measure VTA DA activity (18,22), we confirmed and extended these results to dependent animals experiencing spontaneous withdrawal, showing that tonic DA activity is further decreased during withdrawal from chronic nicotine.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown that tonic DA activity is decreased in nicotine-dependent animals (18) and that precipitated withdrawal from chronic nicotine leads to decreased DA levels (38). Using defined electrophysiological methods to measure VTA DA activity (18,22), we confirmed and extended these results to dependent animals experiencing spontaneous withdrawal, showing that tonic DA activity is further decreased during withdrawal from chronic nicotine.…”
Section: Discussionsupporting
confidence: 74%
“…11 Previous work has shown that dopamine levels are decreased in the NAcc during nicotine withdrawal. 20,21 We hypothesize that nicotine withdrawal activates stress systems in the NAcc, which decreases dopamine levels in this region. As an indirect assessment of changes in dopamine transmission in the NAcc, the present study compared changes in gene expression of dopamine receptors (Drd1, Drd2, and Drd3) during nicotine exposure and withdrawal.…”
Section: Original Investigationmentioning
confidence: 99%
“…Our results are consistent with previous studies in rats showing that nicotine pretreatment increased cocaine-induced reinforcement (McQuown et al, 2007) as well as locomotor sensitization (McQuown et al, 2009) in adolescent but not adult rats. Interestingly, nicotine withdrawal has been shown to differentially regulate extracellular levels of accumbal dopamine in adolescent versus adult rats (Natividad et al, 2010). Likewise, the rewarding actions of nicotine are more pronounced in adolescence compared to adult rats (Natividad et al, 2013).…”
Section: Pk Singh K Lutfymentioning
confidence: 99%
“…Research in the past has shown that nicotine use is initiated during adolescent period and proceeds to the use and abuse of other drugs (Best et al, 2000;Businelle et al, 2013;Carmody et al, 1985;DiFranza and Guerrera, 1990;Lisha et al, 2014;McKee et al, 2011;Rimm et al, 1995;Romberger and Grant, 2004;Torabi et al, 1993;York and Hirsch, 1995). This period of life is a very sensitive age in which the negative affective state associated with nicotine withdrawal is reduced while the rewarding action of nicotine is enhanced compared to adults (Carcoba et al, 2014;Dickson et al, 2014;Dickson et al, 2011;Hutchison and Riley, 2008;Lee et al, 2015;McQuown et al, 2009;Natividad et al, 2012;Natividad et al, 2010;Natividad et al, 2013;O'Dell et al, 2004;O'Dell et al, 2006;O'Dell et al, 2007;Shram et al, 2008;Torres et al, 2008;Wilmouth and Spear, 2004), making adolescents a vulnerable target to nicotine use and abuse as well as for use of other addictive drugs during adulthood. Consistent with this notion, previous studies have shown that nicotine exposure during adolescence can prime the use and abuse of cocaine, alcohol, and other addictive substances (Bechtholt and Mark, 2002;DiFranza and Guerrera, 1990;Horger et al, 1992;Hutchison and Riley, 2008;Kandel and Kandel, 2015;Kandel and Kandel, 2014;Kelley and Rowan, 2004;Kouri et al, 2001;Levine et al, 2011;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation